Marginalized Youth, the 'modern' Professional and the 'modern' Workplace: A note on the Need for a Critical Approach to 'modernizing' Strategies - Paul Michael Garrett (Social Work and Society)
This paper briefly examines plans to "˜transform' social work services for socially marginalized children and young people in England. More specifically, it will focus on moves to privatize social work services for children and young people who are in public care, or "˜looked after'. In what follows, the focus will be on how the promotion of 'social work practices' (SWPs) - the name of these envisaged new structures - is discursively embedded in the idea the idea that "˜liberation' and worker fulfillment can only be delivered within a privatized sphere. In this context, it will be maintained, the work of Boltanski and Chiapello may help to illuminate how the government and other primary definers are seeking to 'win hearts and minds' for further neoliberal "˜transformations' within Children's Services in England.